Analisis Biaya Produksi Sebagai Alat Pengendalian Biaya Produksi Pada CV Mayvajen Abadi - Elfrida Lanu; Maria P. L Muga; Nikson Tameno (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
CV. Mayvajen Abadi is a company engaged in the production of concrete blocks located in Kupang City. In its operations, the company faces various challenges, particularly in managing production costs that directly impact efficiency and profitability levels. This study aims to analyze the role of the production cost budget as a managerial control tool and evaluate cost variances covering raw material costs, direct labor, and factory overhead costs over a five-year period, namely from 2019 to 2023. This study uses a descriptive quantitative approach, by comparing budget data and actual production costs obtained from the company's internal financial reports. The analysis results show significant deviations or variances, especially in the raw material cost component. The increase in raw material costs reached more than 25% from 2021 to 2023. This increase was caused by fluctuations in raw material prices in the market and inefficiencies in the raw material usage process in the field. Meanwhile, labor costs showed relatively good stability, although there were slight fluctuations due to changes in the regional minimum wage. Factory overhead costs vary between years, which are largely influenced by machine maintenance costs, electricity, and other unexpected costs. This instability in production cost control indicates that the budgeting system used is not fully effective as a control tool. Therefore, this study recommends improvements in budget preparation to be more accurate and realistic, accompanied by a regular monitoring system. Strengthening the budget's role as a planning and control tool is expected to improve operational efficiency and the company's overall financial performance.